(untitled) (Research, Society and Development, 2022)
The present work aims to analyze the practical changes listed by PEC 16/2021, which is currently pending approval. Inspired by Claudia Hoerig’s case, the aforementioned amendment proposal brings significant changes to the constitutional text, more specifically to the rules on loss of nationality. PEC’s main goal is to prevent the loss of Brazilian citizenship by anyone who voluntarily acquires another nationality, except in cases of statelessness and express requests. The methodology used consists of an applied research, with a deductive and qualitative approach, with a descriptive objective and the purpose of carrying out a diagnostic research. Analyzing its content, as much as the legislator aims to protect Brazilians residing outside the country, the main question is whether PEC 16/21 is really necessary, to the point that art. 12 of the Constitution already maintains the dual nationality of those who really need to acquire another citizenship to remain in the respective country or exercise some civil right there. In addition, it must be emphasized that Brazil does not allow the extradition of native Brazilians, in a way that, if such changes occur, there is an imminent risk of more people entering the country with the objective of using this institute to not comply with or answer for acts carried out abroad. Furthermore, this stance of Brazil to protect native Brazilians who voluntarily chose to establish a political-legal bond with another State, by developing their legal relations in this place, would ensure, to a certain extent, their impunity.